A group II metabotropic glutamate receptor 3 (mGlu3, GRM3) isoform implicated in schizophrenia interacts with canonical mGlu3 and reduces ligand binding - Garcia-Bea, A; Bermudez, I; Harrison, P; Lane, T (SAGE Publications, 2017)
As well as being expressed as a full-length transcript, the group II metabotropic glutamate receptor 3 (GRM3, mGlu3) gene is expressed as an mRNA isoform which lacks exon 4 (GRM3Δ4) and which is predicted to encode a protein with a novel C terminus (called mGlu3 ∆4). This variant may contribute to the mechanism by which GRM3 acts as a schizophrenia risk gene. However, little is known about the properties or function of mGlu3 ∆4. Here, using transiently transfected HEK293T/17 cells, we confirm that GRM3Δ4 cDNA is translated, with mGlu3 ∆4 existing as a homodimer as well as a monomer, and localising primarily to cell membranes including the plasma membrane. Coimmunoprecipitation shows that mGlu3∆4 interacts with canonical mGlu3. mGlu3∆4 does not bind the mGlu2/3 antagonist [3H]LY341495, but the presence of mGlu3 ∆4 reduces binding of [ 3H]LY341495 to mGlu3, paralleled by a decrease in the abundance of membrane-associated mGlu3. These experiments indicate that mGlu3 ∆4 may negatively modulate mGlu3, and thereby impact on the roles of GRM3/mGlu3 in schizophrenia and as a therapeutic target.